AB1028 Do information sources translates to knowledge in osteoporosis? Corpo study: Comprehending osteoporosis real perception and overview. (23rd January 2014) - Cunha-Miranda, L.; Simões, E.; Fernandes, S.; Gonçalves, N.; Leiria, E.; Nogueira, L.
Abstract : Background: Osteoporosis (OP) is a major public health problem with great impact on patient's quality of life and daily living activities. Knowledge on OP may influence the engagement in preventive measures for the development of the disease and fracture 1, 2 . Objectives: To evaluate information sources and knowledge about OP, comparing three populations: general practitioners (GPs), general population and high risk fracture (HRF) population. Methods: Cross sectional survey was performed including GPs (convenience sample, contacted via email or telephone), subjects representative of Portuguese population aged ≥50 years (selected by random route method, door to door) and HRF population (convenience sample, selected from nursing homes and long term facilities from Portugal). Inclusion criteria for HRF population were age ≥50 years, history of femoral neck fracture on the 24 months prior, absence of cognitive limitations. Descriptive analysis was performed, including relative frequencies for categorical variables and mean ± standard deviation for continuous variables. Results: 194 GPs were included (mean age 51.6±9.9 years, 53.1% female). In general population, 2007 subjects were included (mean age of 65.3±10.4 years, 55.2% female). 419 HRF subjects were included (mean age of 78.3±7.8, 70.4% female). GPs mentioned congresses and clinical meetings (88.7%), followed by medical sales representatives (74.7%) as the most common sources of information on OP. General population referred having heard about OP (80.9%), mostly through television (64.8%) and GPs (41.5%). In HRF population, 80.7% referred having heard about OP, being the most referred information sources GPs (57.8%) and television (29.8%). In a TRUE and FALSE questionnaire, all GPs referred as being TRUE OP is more frequent in women after menopause (100%). In general population, 75.4% acknowledged OP is a bone disease, OP is an unavoidable consequence of aging (43.0%) and for the majority of subjects with OP the mean life expectancy is significantly affected (40.1%). For HRF population, the three most frequently indicated as being TRUE were OP is a bone disease (75.2%), OP is an unavoidable consequence of aging (63.7%) and OP is a joint disease (47.7%). GPs considered fracture (94.8%), height decrease (83.0%) and curvature of the spine (79.9%) as the main OP symptoms. 70.3% of general population mentioned at least one disease symptom, being most commonly pointed pain (82.1%). In HRF population, 76.4% indicated at least one OP symptom, with pain (86.3%) and fracture (81.3%) the most common ones. Conclusions: Despite the awareness about the existence of the disease, there is still a great gap in the knowledge of OP symptoms, severity and consequences. Both general population and HRF population referred GP has one of their sources of information. Strategies for information dissemination could be developed to help increasing GP awareness for this disease that will also help spreading it to the rest of the population. References: von Hurst PR, Wham CA. Attitudes and knowledge about osteoporosis risk prevention: a survey of New Zealand women. Public Health Nutr. 2007;10(7):747-53. Riaz M, Abid N, Patel J, Tariq M, Khan MS, Zuberi L. Knowledge about osteoporosis among healthy women attending a tertiary care hospital. J Pak Med Assoc 2008;58(4):190-4. Disclosure of Interest: None Declared